Using common practices to establish a framework for mobile produce markets in the United States - Christina Kasprzak; Julia Schoonover; Deanna Gallicchio; Lindsey Haynes-Maslow; Leah Vermont; Alice Ammerman; Samina Raja; Laurene Tumiel-Berhalter; Lucia Leone (Journal of Agriculture, Food Systems, and Community Development, 2021)
Access to affordable fruit and vegetables (F&V) remains a challenge within underserved communities across the United States. Mobile produce markets (mobile markets) are a well-accepted and effective strategy for increasing F&V consumption in these communities. Mobile market organizations share similar missions that focus on food, health, and empowerment, participate in incentive programs, offer nutrition education, utilize grassroots-based marketing strategies, prioritize local produce, and sell competitively priced produce through a market style. While mobile markets have become increasingly prevalent, models vary widely. Establishing standardized practices is essential for ensuring the effectiveness and sustainability of this important food access program. This research seeks to identify common practices of established mobile markets and describe the resources they rely on.